Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga) - Y. Mabrouki; A. F. Taybi; G. Chavanon; A. Berrahou; A. Millán (Arxius de Miscel-lània Zoològica)
We present old and new faunistic and distributional data on aquatic Polyphaga (Coleoptera) from the east of Morocco, comprising the Oriental Region and the basin of Moulouya River. A checklist of 91 species belonging to 27 genera and seven families is provided. Ochthebius quadrifossulatus (Hydraenidae) and Pomatinus substriatus (Dryopidae) are new records for the basin of Moulouya River, and Helophorus occidentalis, H. discrepans, H. flavipes, Hydrochus flavipes, Anacena globulus, Enochrus fuscipennis and Hydrobius fuscipes, all belonging to the family Hydrophilidae, and Limnebius furcatus, Ochthebius aeneus and O. merinidicus (all Hydreanidae) are new for the entire studied area of Eastern Morocco. We found a clear dominance of the Palearctic elements, mainly Mediterranean, with a high proportion of Ibero–Maghrebian endemisms. This chorotype pattern is similar to those observed for other macroinvertebrates orders in the same study area.